The common problem of vectorial optimization in the technological safety management - Mykola Chomik; Yevgen Havrylko (Social Development & Security, 2020)
In the work examined: possibility of the use of vectorial optimization at a management technogenic safety; some problem aspects of such use; general issue of vectorial optimization at a management technogenic safety and mathematical formalization of this problem comes true.The marked is caused: by complication and importance of practical problems at military to business, for the decision of that the vehicle of analysis of operations is attracted; by inaccuracy of traditional methods of scalar (onecriterion) optimization at the decision of similar problems; by possibilities of vectorial, multicriterion approach in relation to a search and optimization of administrative decisions at consideration of difficult processes and systems of any nature, including, management technogenic safety.It is set that basic difficulties of decision of vectorial tasks to optimization of decisions in relation to a management technogenic safety are related to the specification of the initial formalized model, with transformation of her to the kind, comfortable for a choice optimal decision. Thus there is a necessity for the decision of three fundamental problems on that the rightness of optimal choice depends in a great deal: choice of principle of optimality; choice of principle of normalization; choice of principle of taking into account of priority.Research results can be drawn on during organization of liquidation of consequences of emergencies of different character and realization of management technogenic safety in the aspect of search of optimal decision of such management, including, during the conduct of operation of Incorporated forces.